2018
DOI: 10.4103/ortho.ijortho_216_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Zoledronic Acid on Histopathology and Recurrence after Extended Curettage in Giant Cell Tumors of Bone: A Comparative Prospective Study

Abstract: Background:Giant cell tumor (GCT) of the bone is known for its locally aggressive behavior and tendency to recur. It is an admixture of rounded or spindle-shaped mononuclear neoplastic stromal cells and multinucleated osteoclast-like giant cells with their proportionate dispersion among the former. Zoledronic acid (a bisphosphonate) is being used in various cancers such as myelomas and metastasis, for osteoporosis with an aim to reduce the resorption of bone, and as an adjuvant treatment for the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…26 Kundu et al compared the efficacy of a preoperative zoledronic acid infusion in two surgicaltreated populations and found that that treated group had a lower recurrence rate along with improved surgical removal of the tumor. 27 Gouin et al prospectively evaluated the efficacy of postoperative zoledronic acid use after extensive curettage and found a low (15%) local recurrence rate. 28 Intravenous zoledronic acid appears to be effective with either pre-or postoperative utilization.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…26 Kundu et al compared the efficacy of a preoperative zoledronic acid infusion in two surgicaltreated populations and found that that treated group had a lower recurrence rate along with improved surgical removal of the tumor. 27 Gouin et al prospectively evaluated the efficacy of postoperative zoledronic acid use after extensive curettage and found a low (15%) local recurrence rate. 28 Intravenous zoledronic acid appears to be effective with either pre-or postoperative utilization.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Recently, there were some studies evaluating the effect of BPs on preventing postoperative recurrence of GCTB 2329. However, to the best of our knowledge, there is no definite direction or consensus on the application of BPs in GCTB.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrences were seen in 1 out of 18 patients in the zoledronic acid group and 4 out of 19 patients in the control group ( p = .47). Curettage tissue showed a decrease in stromal cells and increased calcification in the zoledronic acid group .…”
mentioning
confidence: 91%
“…The benefit of adjuvant zoledronic acid, as well as optimal timing and duration of zoledronic acid treatment, is yet to be determined. The improved mineralization and marginalization leading to easier curettage advocates the use of zoledronic acid in the neoadjuvant setting. In a recent comparative prospective study extended curettage was performed in 37 patients with GCTB with or without three preoperative zoledronic acid infusions (4 mg) at 3‐week intervals.…”
mentioning
confidence: 99%